Die identiteit van Christus se hoëpriesterskap in Hebreërs: ? Wysgerige perspektief (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2012)
This article wants to highlight the underlying ontological issues and distinctions required to gain a better understanding of the familiar term identity. In order to achieve this goal the idea of identity is related to the nature of an entity and its properties. Plato’s account of identity and change paved the way for an enduring philosophical wrestling with this problem. The Dooyeweerd tradition, acknowledging the more-than-functional and multi-functional nature of the identity of an entity helps us to employ the distinction between conceptual knowledge and concept-transcending knowledge in order to understand the nature of identity.In the first part of the article the problem of constancy and change is investigated and described from an epistemological perspective. The second part deals with constancy and change, as illustrated by the way in which the author of the letter to the Hebrews uses this distinction to describe the highpriesthood of Christ. It is argued that the identity or theme of his highpriesthood entails an implicit awareness of the foundational relationship between constancy and change, even though the latter surpasses the former by far. The same applies to Christ’s highpriesthood in the current age, as compared to the age to come.